Drivers of prognosis and clinical trajectories differ between COVID and non-COVID acute hypoxic respiratory failure - Shaun Pienkos; Andrew R. Moore; Jonasel Roque; Alexandria Jensen; Ana Pacheco-Navarro; Katherine M. Lebold; Caitlin Parmer-Chow; Pablo A. Sanchez; Haley Morin; Christian O’Donnell; Tara Ramaswamy; William Collins; et al. (PLoS ONE, 2025)
Purpose Examine non-respiratory comorbidities that may affect prognosis in acute hypoxic respiratory failure (AHRF) and respiratory trajectories, comparing those with COVID and non-COVID etiologies of AHRF. Methods This is a retrospective cohort study of patients with AHRF from COVID and non-COVID etiologies treated with high flow oxygen, noninvasive ventilation, or endotracheal intubation in ICUs in two United States hospitals. Results We compared drivers of prognosis and respiratory trajectories between 241 patients with AHRF from COVID and 99 patients with non-COVID AHRF. Patients with COVID had a lower prevalence of major comorbidities or terminal illness (OR 0.14), neurologic disease (OR 0.19), goals of care limitations (OR 0.54), and shock (OR 0.11). A lower proportion of the COVID group were managed with invasive mechanical ventilation (IMV) early in their AHRF course (OR 0.15); however, fewer COVID patients had improvement in AHRF in the first 7 days (OR 0.49), and a greater proportion of COVID patients required IMV on day 14 (OR 2.57). Additionally, fewer COVID patients died or transitioned to comfort care within 14 days following AHRF onset (OR 0.24), and more COVID patients had severe hypoxemia at end-of-life (OR 2.42). Conclusions Patients with AHRF from COVID had fewer non-respiratory comorbidities or goals of care limitations, more prolonged respiratory failure and higher risk of mortality related to hypoxemia. These differences could explain why patients with COVID AHRF may experience greater benefit from disease-specific therapies targeting AHRF compared to patients with non-COVID AHRF.